KEPRIBADIAN TOKOH UTAMA DALAM NOVEL PRAHARA CINTA ALIA KARYA ARIF YS: KAJIAN PSIKOLOGI SASTRA - Riyani, Ratih Widia; Hudiyono, Yusak; Dahlan, Dahri (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2019)
The purpose of this research to (1) describe the factual structure in the novel Prahara Cinta Alia by Arif YS and (2) describe the personality of the main character in the novel Prahara Cinta Alia by Arif YS. The research uses a qualitative approach with descriptive methods. The research has data in the form of words and quotes, while the data source in the research is the novel Prahara Cinta Alia by Arif YS. Data collection methods and techniques used in reading techniques and recorded techniques using instruments. The data analysis technique used in this study is data reduction, data presentation, and making conclusions. The results of this study refer to the structural elements of the novel which are intrinsic and extrinsic and the personality changes of the main characters in the novel Prahra Cinta Alia by Arif YS.